Inaccurate Space Perception Seeing Through Fences. (September 2020) - Dong, Bo; Chen, Airui; Zhang, Yuting; Li, Changchun; Zhang, Tianyang; Zhang, Ming
According to the sequential surface integration process hypothesis, the fine near-ground-surface representation and the homogeneous ground surface play a vital role in the representation of the ground surface. When an occluding box or opaque wall is placed between observers and targets, observers underestimate egocentric distance. However, in our daily life, many obstacles are perforated and cover the ground surface and targets simultaneously (e.g., fences). Humans see and observe through fences. The images of these fences and targets, projected onto observers' retinas, overlap each other. This study aims to explore the effects of perforated obstacles (i.e., fences) on space perception. The results showed that observers underestimated the egocentric distances when there was a fence on the ground surface relative to the no-fence condition, and the effect of widely spaced thick wood fences was larger than that of narrowly spaced thin iron fences. We further demonstrated that this effect was quite robust when the target size had a visual angle of 1°, 2°, or 4° in three virtual reality experiments. This study may add support for the notion that the sequential surface integration process hypothesis is applicable even if the obstacle is perforated and covers the target.